2017
DOI: 10.1002/mabi.201700273
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Nanoparticles Induce NLRP3 Inflammasome Activation and Promote Breast Cancer Metastasis

Abstract: Polymeric nanoparticles gain enormous interests in cancer therapy. Polyethylenimine (PEI) 25 kD is well known for its high transfection efficiency and cytotoxicity. PEI-CyD (PC) was previously synthesized by conjugating low molecular PEI (M 600) with β-cyclodextrin (β-CyD), which is shown to induce lower cytotoxicity than PEI 25 kD. In the current study, the in vivo immune response of branched PEI 25 kD and PC is investigated. Compared to PC/pDNA, exposure of PEI 25kD/pDNA induces higher level of immune-stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…Clearly, NLRP3 inflammasome activation performed a dual role in cancers . Reports indicated that activated NLRP3 inflammasome contributed to the matastasis of breast cancer and the progression of late stage of melanoma, but it acted as a negative regulator in human hepatocellular carcinoma and colorectal cancer . In our present study, NLRP3 inflammasome activation was demonstrated to play an important role in promoting inflammation‐related lung cancer in vitro, this result was supported by previous studies that NLRP3 inflammasome was upregulated in lung adenocarcinoma and small cell lung cancer in vivo .…”
Section: Discussionsupporting
confidence: 89%
“…Clearly, NLRP3 inflammasome activation performed a dual role in cancers . Reports indicated that activated NLRP3 inflammasome contributed to the matastasis of breast cancer and the progression of late stage of melanoma, but it acted as a negative regulator in human hepatocellular carcinoma and colorectal cancer . In our present study, NLRP3 inflammasome activation was demonstrated to play an important role in promoting inflammation‐related lung cancer in vitro, this result was supported by previous studies that NLRP3 inflammasome was upregulated in lung adenocarcinoma and small cell lung cancer in vivo .…”
Section: Discussionsupporting
confidence: 89%
“…10,11,14 This versatile family of materials has been utilized for delivery of siRNA, 10-12, 15 peptides and proteins, 8,16,17 hydrophilic small molecules, 18 and RNA immunotherapeutics, 19,20 with several of these polymers having been demonstrated to be well-tolerated in pre-clinical animal studies. 16,17,[20][21][22] However, it is also known that many micro-and nanoparticles (e.g., alum, 23,24 and silica 25 ) as well as commonly used cationic drug carriers such as PEI 26 and chitosan, 27,28 can induce inflammatory responses via activation of the inflammasome. The inflammasome is a multiprotein complex that is activated in response to cellular stress.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the unique properties of engineered material, oxidative stress has been widely reported for triggering cell damage and death in vitro and in vivo . To explore whether the developmental toxicity induced by GO could be ascribed to oxidative stress response, oxidative markers and antioxidant enzyme activities were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoparticles were widely reported for their serious side effects . For GO, contrasting results about its toxicity have been observed.…”
Section: Introductionmentioning
confidence: 99%